Fabrication and characterization of tungsten-brass composite using powder metallurgy process - Gowon, Baba (School of Materials Engineering, 2016)
The objectives of this work are; to study the effects of Ni and Fe transition element addition, as sintering activators on the densification and microstructure of W-brass pre-mixed and pre-alloyed composites; to study the effects of the main sintering parameters, such as sintering temperature and time on the densification of different pre-mixed and pre-alloyed W-brass composites; to investigate the effects of mechanically activated sintering (mechanical alloying) on the densification of W-brass composites.